2022
DOI: 10.1007/s13202-022-01554-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 on the interfacial tension and swelling of crude oil during carbonated water flooding

Abstract: Since the influence of carbon dioxide (CO2) on the dynamic interfacial tension of crude oil and aqueous solutions at the elevated temperatures and pressures is an important issue, this investigation is aimed to measure the IFT of crude oil/water, CO2, and carbonated water. The measured values reveal that the IFTs of crude oil/CO2 are decreased through the first interval, while a gradual and continuous reduction in IFT is obtained at the second interval. Although both intercepts and slopes of the first interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The inverse relationship between crude oil's swelling factor and the interfacial tension and viscosity of CO 2 -saturated crude oil at pressures up to 1000 psi is supported by the trends depicted in Figures 9, 6, and 8, as observed by numerous previous research findings. 72,73 3.5. Design of PAG Cycle.…”
Section: Viscosity Reductionmentioning
confidence: 99%
“…The inverse relationship between crude oil's swelling factor and the interfacial tension and viscosity of CO 2 -saturated crude oil at pressures up to 1000 psi is supported by the trends depicted in Figures 9, 6, and 8, as observed by numerous previous research findings. 72,73 3.5. Design of PAG Cycle.…”
Section: Viscosity Reductionmentioning
confidence: 99%
“…Crude oil can expand by 30% in 2 h when supercritical CO 2 is absorbed, but it takes 5 times longer to achieve a similar effect when gaseous CO 2 is absorbed. In addition, Farahabadi and Lashkarbolooki found that the expansion coefficient did not change significantly at different temperatures under 500 psi pressure, but the expansion coefficient increased when the pressure was 4500 psi. Meanwhile, the expansion coefficient also increased when the temperature increased, and other conditions remained unchanged.…”
Section: Co2 Floodingmentioning
confidence: 99%